New Results and Generalizations for Approximate Fixed Point Property and Their Applications - Wei-Shih Du; Farshid Khojasteh (Abstract and Applied Analysis)
We first introduce the concept of manageable functions and then prove some new existence theorems related to approximate fixed point property for manageable functions and α-admissible multivalued maps. As applications of our results, some new fixed point theorems which generalize and improve Du's fixed point theorem, Berinde-Berinde's fixed point theorem, Mizoguchi-Takahashi's fixed point theorem, and Nadler's fixed point theorem and some well-known results in the literature are given.